Star photometry with all-sky cameras to retrieve aerosol optical depth at nighttime - R. Román; R. Román; D. González-Fernández; D. González-Fernández; J. C. Antuña-Sánchez; J. C. Antuña-Sánchez; C. Herrero del Barrio; C. Herrero del Barrio; S. Herrero-Anta; S. Herrero-Anta; Á. Barreto; Á. Barreto; et al. (Atmospheric Measurement Techniques, 2025)
The lack of aerosol optical depth (AOD) data at night can be partially addressed through Moon photometer measurements or fully covered with star photometer observations. However, the limited availability and complexity of star photometers have motivated this study to use all-sky cameras to extract starlight signals and derive AOD at night using star photometry. For this purpose, eight all-sky cameras were configured and deployed in nine different locations to capture raw images with varying exposure times every 2 min during the night. This work proposes a novel methodology to extract the starlight signal from the raw data from all-sky cameras and convert it into AOD values. This process consists of the following steps: removing the background image, selecting the pixels, and extracting the signal for each star from a predefined list of 56 stars; performing in situ Langley calibration of the instruments and retrieving the total optical depth (TOD); calculating the effective wavelength for each camera channel; deriving the AOD by subtracting the gas contribution to TOD; and averaging, cloud-screening, and quality-assuring the AOD time series. The AOD time series obtained through this methodology are compared with independent AOD measurements from collocated Moon photometers in the nine locations. The obtained results show that the AOD values derived with the proposed method generally correlate with reference values, often achieving correlation coefficients (r) above 0.90. The AOD values retrieved using the cameras tend to overestimate the reference values by approximately 0.02 and exhibit a precision of around 0.03–0.04. The agreement between the two datasets varies with wavelength and decreases at high-latitude locations, likely due to the poorer performance of Langley calibration in these regions. AOD values align well with day-to-night transitions obtained by solar photometers, demonstrating their reliability. Despite the slight overestimation, the AOD values derived by this new method approximate the real values and provide coverage throughout the entire night, without requiring the presence of the Moon. Therefore, they serve to study and monitor the nocturnal evolution of AOD.